SOIL SEED BANK COMPATIBILITY WITH ABOVEGROUND PLANTS UNDER DIFFERENT TOPOGRAPHICAL PARAMETERS IN THE ZAWITA MOUNTAINS FOREST - AHMED, GAILAN BAPER; KHALAF, AHMED SALIH; SHABAZ, SALEEM ISMAEL (Journal of Duhok University, 2022)
One of the strategies for survival and distribution of individual species in natural regeneration which is affected by environmental factors. The vegetation covers and seedling’s emergence from the soil bank were studied by the effect of topographical factors (aspects, elevation, and slope gradient), in the forest` of Zawita mountains, and the Sorensen similarity index was estimated between vegetation cover and soil seed bank. The experiment was factorial with a strip-split plot design and four blocks. The results are summarized by the identification of 109 species belonging to 25 families with both vegetation and soil seed bank in the south aspect, while in the north aspect, 138 species combined with vegetation and soil seed bank, which were belongs to 29 families. The results recorded that the highest density of plants and species richness in the north aspect increased significantly with increasing elevation (214.92 and 246.72 plants.m-2), (20.79 and 19.94) respectively. While the highest density of seed banks emerged and species richness was recorded in the south aspect with increasing in the elevation and low slope gradient (3554.9, 2778.41, and 2692.59 plant.m-2), (16.75, 16.88, and 17.58) respectively. The degree of similarity with the Sorensen index between vegetation cover and soil seed bank was low under these topographical variables